Вузловий зоб: сучасні аспекти діагностики та лікування - Паньків, В. І. (Clinical Endocrinology and Endocrine Surgery, 2010)
Lecture covers questions of terminology, pathogenesis, diagnostics, differential diagnosis and treatment of various forms of thyroid nodular lesions.